The Legal Protection of the Right to Digital Privacy in Algeria - Guedda, Hanane; Chabane, Fadhila (Journal of Ecohumanism, 2025)
This paper addresses the legal protection of the right to digital privacy in Algeria. This topic holds great importance due to the growing challenges and threats faced by this right in the digital sphere. In response, the Algerian legislator has established a constitutional and legal framework to ensure its effective protection amid the rapidly evolving technological revolution. The Constitution first guarantees citizens the right to privacy, followed by the right to the confidentiality of their communications and correspondence in all forms. To implement these protections, the legislator enacted Law No. 18-07 on the protection of natural persons in the processing of personal data, and created an independent authority responsible for safeguarding individuals’ rights, freedoms, and private lives from the risks posed by information and communication technologies.